Enhancing Payment Security For SMEs In Global Trade Trough Letter Of Credit: A Case Study Of Chip Producer In Batu - Hidayati, Irma; Sudarmiatin Sudarmiatin (International Journal of Economics, Business and Innovation Research, 2024)
Small and medium-sized enterprises (SMEs) play a pivotal role in global trade, but they face significant challenges, particularly in managing payment risks. This study investigates the role of Letters of Credit (LCs) in enhancing payment security and financial stability for SMEs in international trade, using a case study of PT. ATN, an SME located in Batu Malang, Indonesia. The research aims to explore how LCs mitigate payment risks, improve operational stability, and facilitate participation in global markets. A qualitative research methodology was employed, utilizing semi-structured interviews and documentary analysis. Data were analyzed thematically to identify key challenges, benefits, and the broader implications of LC utilization. The study also examined the operational processes involved in LC issuance, including the critical role of banks as intermediaries. The findings reveal that LCs significantly reduce payment uncertainties and enhance cash flow stability for SMEs. By ensuring payment through third-party bank guarantees, LCs provide a financial safety net that enables SMEs to focus on market expansion and productivity improvements. However, challenges such as stringent documentation requirements and complex procedures hinder their wider adoption. Institutional support, including trade fairs and export facilitation programs, was identified as critical in connecting SMEs with international buyers and supporting LC usage. This study contributes to the existing literature by providing empirical insights into the practical applications and challenges of LCs in emerging markets. It underscores the need for targeted training and the integration of digital technologies to streamline LC processes. These findings have important implications for policymakers and financial institutions seeking to empower SMEs in the global trade landscape